Elementary School Library Automation System Implementation - Bhakti, Muhammad Agni Catur; Mantoro, Teddy; Ayu, Media Anugerah; Tarigan, William Hazkel; Effendi, Nicholas Lasca; Wandy, Wandy (Journal of Community Services: Sustainability and Empowerment, 2022)
A library is essential in education, especially in elementary schools. SD Negeri Rambutan 03 Pagi Jakarta is a public school in East Jakarta with a library. The school library was managed manually, where books with detailed information were stored on a spreadsheet. Some library processes could not perform well, such as tracing how many books were on loan. Based on this situation, a library management system was required to support library activities. Sampoerna University had several collaborations with SD Negeri Rambutan 03 Pagi Jakarta for community services, a workshop, and an internship. In this community service opportunity, We used a qualitative method with internal discussions and literature reviews. We provided a dedicated server machine to be placed on-premise. This machine will be a library automation system over the school's Local Area Network (LAN). Senayan Library Management System (SLiMS) was chosen to be installed on the server because it has the required features to support the school library. One of the essential things is that SLiMS is free and open source. The library automation system has been successfully implemented, and there will be future community service activities to continue the library system development.